Differentiated Learning in the Independent Curriculum to Enhance Mathematical Connection and Resilience of State Junior High School Students in East Kalimantan Province - Abdul Razak; Rumainur (Universitas Veteran Bangun Nusantara, 2025)
This quasi-experimental study aims to analyze the effectiveness of differentiated learning within the Merdeka Curriculum in enhancing the mathematical connection and resilience of junior high school students in East Kalimantan Province. The research employed a pretest-posttest control group design, involving purposively selected eighth-grade students from several public schools. Data was collected through a mathematical connection test, a resilience questionnaire, and learning process observations. The results indicate that differentiated learning significantly improved students' mathematical connection and resilience compared to conventional instruction. The experimental group's average mathematical connection score increased from a low to a high category, with notable improvements in their ability to relate mathematical concepts to daily life and other mathematical ideas. Furthermore, students demonstrated significantly enhanced mathematical resilience, particularly in perseverance, problem-solving persistence, and adaptability to challenges. Key success factors included needs-based lesson planning, active student engagement, and motivating reflective practices.In conclusion, Differentiated instruction is effective in significantly increasing the mathematical resilience of eighth-grade students in East Kalimantan, with a significant value of 0.000 < 0.05. Differentiated instruction is effective in significantly increasing the mathematical connection of eighth-grade students in East Kalimantan, with a significance value of 0.000 < 0.05.Differentiated instruction is effective in simultaneously and significantly increasing both the mathematical resilience and mathematical connection of eighth-grade students in East Kalimantan, with a significance value of 0.000 < 0.05. It is recommended that teachers adopt differentiated strategies more widely to support inclusive, meaningful learning and develop student competencies in the era of independent learning.